Comparative study of transitional speed in amateur footballers by playing positions - hemimi, Djamel; khelfaoui , lazhari (sports creativity, 2024)
The aim of the study was to find out whether there were statistical differences in the transitory speed profile of footballers depending on the different playing positions. The researcher used the comparative descriptive curriculum. The sample study included 18 players for the intentionally selected amateur team (6 defenders; 6 midfielders; 6 forwards), the sample conducted a 30 metre speed test as a study tool, the results showed no statistically significant differences in the transition speed of the team players by their playing positions The researcher concluded that there were no statistically significant differences in the 30-metre speed profile depending on the playing positions and that great importance must be attached to the development of this physical character of modern football and the need to attach great importance to specialized training according to the requirements of each position.